EFEKTIVITAS PENCATATAN NIKAH BERBASIS SIMKAH DI KUA KECAMATAN GUDO TAHUN 2023 - M. Hafiz Nur Fajri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of information technology has brought significant changes in various aspects of life, including marriage administration processes. The recording of marriages based on the Marriage Management Information System (SIMKAH) at the Office of Religious Affairs (KUA) of Gudo Subdistrict, Jombang Regency in 2023 is the primary focus of this research. This study aims to identify factors that support and inhibit the effectiveness of SIMKAH in marriage registration and to evaluate the extent of SIMKAH effectiveness in the marriage registration process at KUA Gudo. The research examines the concept of effectiveness in the context of marriage registration, using SIMKAH as a case study at KUA Gudo Subdistrict, Jombang Regency in 2023. Effectiveness is understood from various perspectives, ranging from general definitions to specific applications in Islamic law related to marriage registration. The research method employed is qualitative with a field study approach. Data were obtained through in-depth interviews with KUA staff, direct observation, and study of relevant documents.The results of the research show that the implementation of online SIMKAH (Marriage Registration Information System) has been successful due to several key factors. First, the accessibility provided by the SIMKAH Web application allows people to register marriages online without needing to visit the KUA office in person. Second, the user-friendly design of the SIMKAH Web platform assists users in the marriage registration process without technical difficulties. Third, the use of SIMKAH Web improves data accuracy and consistency with minimal input errors. Fourth, SIMKAH Web saves time and costs through an efficient online registration process. However, there are inhibiting factors that hinder marriage registration based on SIMKAH at KUA Gudo. Lack of public awareness, technological limitations, and internet network disruptions pose significant challenges. Intensive socialization, education, technology training, and improvement of internet infrastructure are required to overcome these obstacles. Addressing these inhibiting factors will enhance the efficiency of SIMKAH implementation at KUA Gudo and maximize benefits for the community in electronic marriage registration processes.